Understanding the traveling behavior of Muslims in the United States. Issue 1 (2nd March 2015) - Yvette Reisinger, Dr Omar Moufakkir, Dr; Shakona, Maloud; Backman, Kenneth; Backman, Sheila; Norman, William; Luo, Ye; Duffy, Lauren
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the influence of Islamic beliefs and practices on leisure and travel behavior of Muslims in Clemson, South Carolina. With the increase of Muslims in the USA, from both conversion and immigration, it is important to examine the effects of their religion on leisure and travel behavior. Design/methodology/approach – Using the grounded theory approach, semi-structured interviews with six Muslim men and six Muslim women of different nationalities were conducted in English in the local Mosque of Clemson, South Carolina, in the fall of 2011. Findings – The results provide some evidence that Islamic beliefs and behavioral practices influence leisure and travel behavior of Muslims in the USA. The study identifies seven major themes that play an important role in determining leisure and travel behavior of Muslims in Clemson. These are the importance of mosques, traveling with a Mohram, Hijab and a dress code for men and women, drinking alcohol and being in places where alcohol is served, eating pork, Holy Month of Ramadan and Dabiha. Practical implications – The study highlights the need for tourism marketers to pay more attention to the influence of religion on leisure and travel behavior of Muslim travelers. Originality/value – The study provides the tourism industry with a better understanding of the importance of religion influences on the special needs of Muslim travelers and shows how the industry can better accommodate these needs.